Implantação das práticas integrativas e complementares no sistema único de saúde na perspectiva de profissionais da atenção primária à saúde - Beneli, Fabiana Zucchi (Universidade Federal de São Carlos, 2023)
Integrative and complementary practices (PIC) in the SUS are recognized for their scope in a holistic care based on comprehensiveness. In this direction, this research had the general objective of analyzing the process of creation and implementation of PICs in the SUS in the municipalities that are part of the Regional Department of Health III (DRS III) of the State of São Paulo. The specific objectives were to identify the offer of PICs in the SUS and analyze the factors that facilitate and hinder this offer in municipalities that are part of the DRS III, in the State of São Paulo. This is a descriptive study, with a qualitative approach, developed through action research (AP), carried out in 12 municipalities that are part of the DRS III. Fifteen health professionals who offer PIC in the SUS of the respective municipalities participated in the research. Data collected through an online questionnaire and face-to-face workshops, between July and December 2022, were studied using thematic content analysis. The most offered PICs are, respectively, auriculotherapy, reiki and floral therapy. The offer is multidisciplinary, with the majority being community health agents, followed by nursing, pharmacists, physocolgist and occupational therapy professionals. ICP training is predominantly self-funded by participants professionals. From the interaction with the participants and the research data, two promotional materials and a scientific article were produced. The dissemination materials consist of a mapping of the PICs in the SUS of the DRS III and a folder of the PICs offered in the region and their benefits, reported by the professionals in their day-to-day work in the SUS. The scientific article presents the following main actors: health professionals, the municipal health council and health managers at the municipal leve in the process of creation and implementation of the PICs and observed that the Family Health Strategy Program is the health establishment of the SUS that primarily offers these therapeutic approaches. From the thematic content analysis, two themes emerged: 'An ongoing support story and its interfaces' and 'Between complementary and main, in an expanded perspective of health'. The dissemination of PICs in the region can favor knowledge and planning of PIC actions in the municipalities of SUS. Despite the lack of support, both in the offer and in the institutionalization of PICs and its national policy, the municipal experiences in the region studied demonstrate a new history of support for these approaches in the daily life of SUS services, experienced by users and health professionals. And the PICs, as the main choice of care, in an expanded and holistic perspective, denote the technological innovation of this turn of the millennium and are the expression of the exercise of citizenship and the SUS in defense of life.
Implementation of integrative and complementary practices in the unified health system from the perspective of primary health care professionals
Keywords: Terapias Complementares; Atenção Primária à Saúde; Integralidade em Saúde; Complementary Therapies; Complementary Therapies; Unified Health System; Primary Health Care; Integrality in Health; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE; CIENCIAS DA SAUDE::ENFERMAGEM; 3. Saúde e Bem-Estar